EXPLORING ENTREPRENEURIAL NARRATIVES: A QUALITATIVE SWOT-BASED ANALYSIS OF PROMOTIONAL STRATEGIES AT WARUNG JOYOBOYO - Gazza Aimar Degadypta; Anita Sumelvia Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research aims to formulate effective promotional strategies for MSME Warung Joyoboyo Kediri using a descriptive qualitative approach based on case studies. MSME Warung Joyoboyo Kediri faces intense competition and changing consumer preferences, requiring appropriate promotional strategies. Through in-depth interviews, field observations, and documentation, data was analyzed through data reduction, data presentation, and conclusion drawing, with data validity testing using source triangulation. The data was then classified into SWOT (Strengths, Weaknesses, Opportunities, Threats) categories. Research results show that the main strengths lie in distinctive taste and affordable prices, while weaknesses include digital promotion and recording systems. Available opportunities include social media trends and government support, while threats come from similar competitors and raw material price fluctuations. This research contributes to formulating locally-based promotional strategies for MSME.